2020
DOI: 10.20944/preprints202005.0342.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroprotective Potentials of Marine Algae and Their Bioactive Metabolites: Pharmacological Insights and Therapeutic Advances

Abstract: Beyond their significant contribution to the dietary and industrial supplies, marine algae are considered to be a potential source of some unique metabolites with diverse health benefits. The pharmacological properties, such as antioxidant, anti-inflammatory, cholesterol homeostasis, protein clearance and anti-amyloidogenic potentials of algal metabolites endorse their protective efficacy against oxidative stress, neuroinflammation, mitochondrial dysfunction, and impaired proteostasis which are known t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 210 publications
(293 reference statements)
0
30
0
Order By: Relevance
“…Another source of marine compounds with antioxidant activity is seaweeds, which have been the target of numerous studies (extensively reviewed in [ 121 ]), standing out as major producers of bioactive molecules with high antioxidant ability. Another research group tested the effects of different seaweed extracts ( S. muticum.…”
Section: Marine Drugs In Parkinson’s Diseasementioning
confidence: 99%
“…Another source of marine compounds with antioxidant activity is seaweeds, which have been the target of numerous studies (extensively reviewed in [ 121 ]), standing out as major producers of bioactive molecules with high antioxidant ability. Another research group tested the effects of different seaweed extracts ( S. muticum.…”
Section: Marine Drugs In Parkinson’s Diseasementioning
confidence: 99%
“…Algae metabolites are known to have cytostatic, antiviral, anthelmintic, antifungal and antibacterial activity [ 1 , 2 ]. High biological activity of algae is often associated with the presence of powerful and non-toxic natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the downstream phosphorylation of ERK, which is a mitogen-activated protein kinase (MAPK), activated CREB transcription, regulating the expression of BDNF [ 35 , 36 ]. In contrast, the phosphorylation of JNK and p38, which are also MAPKs, leads to apoptosis and cell death [ 37 , 38 ]. Based on these results, we suggest that ERK may promote the expression of BDNF and TrkB in oxidative stress-induced HT-22 cells.…”
Section: Discussionmentioning
confidence: 99%